Speech Therapy for children with hearing loss: When does it ends? - Kyriakoy, Andrea; Grigoriadi, Konstantina; Binos, Paris (My University, 2024)
The presentation explores the process, goals, and duration of speech therapy for children with hearing impairments. Early intervention is emphasized as a crucial factor for successful language and communication development. The therapy focuses on improving articulation, language comprehension, and social communication skills. It includes auditory training, the use of hearing technology, and family involvement. The duration of speech therapy varies based on the severity of hearing loss, the age of diagnosis, and the support from home and school environments. The goals of therapy are structured using the S.M.A.R.T. framework, evidence-based practices, targeting age-appropriate language development and effective communication. Regular progress assessments ensure the therapy is tailored to each child's needs. Speech therapy typically concludes when the child can function independently across different settings, such as home, school, and social environments. However, therapy may continue periodically during critical transitions in a child’s life. The active involvement of family and educators is crucial in facilitating continuous progress and ensuring a successful transition after therapy ends.